Next-Generation Drug Delivery Strategies for Personalized Healthcare - Shende, Shubham; Devhare, Lalchand; Prasad, Chandani; Khobragade, Ashish; Khapne, Ajit (Pharmaceutical Research - Recent Advances and Trends Vol. 2, 2024)
The advent of personalized medicine has revolutionized healthcare, allowing tailored treatment plans based on individual patient characteristics. Central to this paradigm shift are advanced drug delivery strategies designed to enhance therapeutic efficacy, minimize side effects, and improve patient outcomes. This review paper provides a comprehensive overview of next-generation drug delivery approaches, focusing on their application in personalized healthcare. We discuss various strategies, including nanomedicine, targeted drug delivery systems, stimuli-responsive delivery systems, and biomaterial-based platforms, highlighting their potential to address the challenges of conventional drug administration methods. Furthermore, we examine the integration of personalized diagnostics and therapeutics, emphasizing the importance of precision medicine in optimizing treatment regimens for individual patients. Overall, this review underscores the critical role of innovative drug delivery technologies in advancing personalized healthcare and shaping the future of medicine.